2021
DOI: 10.1021/acsmacrolett.1c00255
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Designed Additives for Chemically Deconstructable Thermosets without Compromised Thermomechanical Properties

Abstract: Metrics & MoreArticle Recommendations * sı Supporting Information ABSTRACT: "Drop-in" additives that introduce chemically cleavable bonds into thermosets without compromising thermomechanical properties could enable triggered material deconstruction and enhanced sustainability. While the installation of cleavable bonds into the strands of the commercial thermoset polydicyclopentadiene (pDCPD) using comonomers facilitates chemical deconstruction, these additives can lower the material's glass transition tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 35 publications
1
47
0
Order By: Relevance
“…24 They demonstrated that crosslinked polydicyclopentadiene synthesized by ringopening metathesis polymerization underwent a complete degradation after addition of only 10 mol% of a silyl ether-based, cleavable comonomer. [24][25][26] In the case of vinyl polymers, degradable bonds can be installed in the backbone by radical ring-opening polymerization (RROP) of cyclic monomers such as cyclic ketene acetals or allyl sulfide lactones. [27][28][29][30][31] Thionolactones, such as dibenzo[c,e]oxepane-5-thione (DOT) have been recently presented as a degradable comonomer which undergo RROP with acrylates, acrylamides, acrylonitrile, [32][33][34][35] as well as vinyl esters, 36 styrene and methacrylates.…”
mentioning
confidence: 99%
“…24 They demonstrated that crosslinked polydicyclopentadiene synthesized by ringopening metathesis polymerization underwent a complete degradation after addition of only 10 mol% of a silyl ether-based, cleavable comonomer. [24][25][26] In the case of vinyl polymers, degradable bonds can be installed in the backbone by radical ring-opening polymerization (RROP) of cyclic monomers such as cyclic ketene acetals or allyl sulfide lactones. [27][28][29][30][31] Thionolactones, such as dibenzo[c,e]oxepane-5-thione (DOT) have been recently presented as a degradable comonomer which undergo RROP with acrylates, acrylamides, acrylonitrile, [32][33][34][35] as well as vinyl esters, 36 styrene and methacrylates.…”
mentioning
confidence: 99%
“…Our group previously reported that 8- and 7-member cyclic bifunctional silyl ether olefins could be efficiently prepared and statistically copolymerized with a variety of ROMP-active norbornene derivatives with potential applications in drug delivery and recyclable thermosets. 12,14,15 At the concentrations at which these copolymerizations were previously conducted (50 mM), however, these monomers were not found to homopolymerize. 12 Stemming from this observation, we sought to identify conditions under which these monomers could be homopolymerized as we anticipated their respective polymers would possess desirable properties including facile deconstructability and thermal properties akin to polydimethylsiloxane (PDMS).…”
mentioning
confidence: 94%
“…The combination of DOT/acrylate polymerization and VAT photopolymerization could be an efficient way to prepare (bio)degradable 3D objects. It has been shown that only few percent (5-10 vol %) of cleavable units are required to impart degradability of thermosets [28,29] and also that DOT has a slightly higher rate of incorporation [33] than acrylate derivatives during their copolymerization, making it possible to use a very low amount of DOT as additive.…”
Section: Introductionmentioning
confidence: 99%